Studi Kualitas Air, Status Mutu Air dan Beban Pencemaran Sungai Badung - Bernard A.R Mendes; I Wayan Suarna; I Made Sara Wijana (Fakultas Teknik Universitas Cenderawasih, 2024)
This study aims to analyze the water quality of the Badung River based on Class II River water quality standards according to Government Regulation No. 22 of 2021, determine the water quality status, and calculate the potential pollution load of the Badung River. Water quality measurements were conducted at five sampling points. The parameters measured and observed include Temperature, Total Suspended Solids (TSS), pH, Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Dissolved Oxygen (DO), Sulfate (SO42), Nitrate (NO3), Total Phosphate (P), Oil & Grease, Total Detergent, and Total Coliform. Samples were analyzed in the laboratory for physical, chemical, and microbiological parameters. The water quality status of the Badung River was determined using the pollution index method, and the potential pollution load was calculated using the wastewater emission coefficient approach. The results showed that the water quality and status of the Badung River are classified as lightly polluted, with an average pollution index value of 3.65. The potential pollution load entering the Badung River in the domestic sector is 0.78 tons/day for BOD, 1.07 tons/day for COD, and 0.74 tons/day for TSS. Factors contributing to the lightly polluted water quality status include population density, poorly managed domestic activities (household waste), which contribute to high pollution parameter values such as BOD, COD, and TSS, and a lack of waste management infrastructure